2018
DOI: 10.1111/febs.14634
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the GTP‐dependent allosteric control of c‐di‐GMP hydrolysis from the crystal structure of PA0575 protein from Pseudomonas aeruginosa

Abstract: Bis-(3'-5')-cyclic diguanylic acid (c-di-GMP) belongs to the class of cyclic dinucleotides, key carriers of cellular information in prokaryotic and eukaryotic signal transduction pathways. In bacteria, the intracellular levels of c-di-GMP and their complex physiological outputs are dynamically regulated by environmental and internal stimuli, which control the antagonistic activities of diguanylate cyclases (DGCs) and c-di-GMP specific phosphodiesterases (PDEs). Allostery is one of the major modulators of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 61 publications
(149 reference statements)
2
36
0
9
Order By: Relevance
“…Because only three genomes had partial EAL domains, the EAL domain in hybrid proteins from the M. aeruginosa NIES843 genome were chosen as paradigms to examine the crystal structure. Based on the crystal structure of the GGDEF-EAL domain of RmcA (PDB ID: 5M3C), which has a crystallographic resolution of 2.8 Å [54], the GGDEF and EAL domains in the hybrid protein of NIES843 were modeled. Compared with 5M3C, the GGDEF-EAL domains in the hybrid proteins showed sequence conservation of 35.9-37.8% (Additional file 1, Table S9).…”
Section: Structural Features Of Ggdef Domain Eal Domain and Hd-gyp mentioning
confidence: 99%
See 1 more Smart Citation
“…Because only three genomes had partial EAL domains, the EAL domain in hybrid proteins from the M. aeruginosa NIES843 genome were chosen as paradigms to examine the crystal structure. Based on the crystal structure of the GGDEF-EAL domain of RmcA (PDB ID: 5M3C), which has a crystallographic resolution of 2.8 Å [54], the GGDEF and EAL domains in the hybrid protein of NIES843 were modeled. Compared with 5M3C, the GGDEF-EAL domains in the hybrid proteins showed sequence conservation of 35.9-37.8% (Additional file 1, Table S9).…”
Section: Structural Features Of Ggdef Domain Eal Domain and Hd-gyp mentioning
confidence: 99%
“…In this platform, templates are ranked based on the expected quality of the resulting models, and estimated by Global Model Quality Estimate and Quaternary Structure Quality Estimate [88,89]. The crystal structures of a DGC (WspR) from P. aeruginosa [52], the GG[D/E]EF-EAL hybrid domain protein RmcA from P. aeruginosa [54], the HD-GYP domain containing protein PA4781 from P. aeruginosa [56], and the PilZ domain-containing protein BcsA from R. sphaeroides were selected as templates for the structural analyses [31]. QMEAN scoring functions were used to estimate alternative models and screen for models whose scores strongly matched highresolution structures that were then used to create the corresponding model [90].…”
Section: Proteins Structural Analysesmentioning
confidence: 99%
“…aeruginosa [52], the GG[D/E]EF-EAL hybrid domain protein RmcA from P. aeruginosa [54], the HD-GYP domain containing protein PA4781 from P. aeruginosa [57], and the PilZ domain-containing protein…”
Section: Proteins Structural Analysesmentioning
confidence: 99%
“…5a (left), the WebLogo alignment revealed that the RXXD and GGEEF motifs of the GGEEF domain were highly conserved in the same amino acid residues: Arg-EF domain of the putative DGCs possessed the conserved amino acid residues essential for GTP binding, indicating that the DGCs may have catalytic activity[26].Because only three genomes had partial EAL domains, the EAL domain in hybrid proteins from the M. aeruginosa NIES843 genome were chosen as paradigms to examine the crystal structure. Based on the crystal structure of the GGDEF-EAL domain of RmcA (PDB ID: 5M3C), which has a crystallographic resolution of 2.8 Å[54], the GGDEF and EAL domains in the hybrid protein of NIES843 were modeled.…”
mentioning
confidence: 99%
“…In P. aeruginosa PAO1, twelve genes code for proteins with PAS domains linked to DGC domains, nine of which additionally contain PDE domains 5 , namely pa0285, pa0290, pa0338, pa0575 9 , pa0847, pa0861 ( rbdA 10 ), pa1181 ( yegE ), pa2072 , pa4601 ( morA 1113 ), pa4959 ( fimX 14 ), pa5017 ( dipA 15 ), and pa5442 . The recurrence of proteins with similar architecture, and which play a role in biofilm regulation, poses two key questions: Firstly, if DGCs and PDEs regulate the transition between sessility and the planktonic state, how do the specific protein sensory domains then control mechanisms of motility?…”
Section: Introductionmentioning
confidence: 99%